Effects of crumb rubber size and percentage on degradation reduction of railway ballast. (10th July 2019) - Guo, Yunlong; Markine, Valeri; Qiang, Weile; Zhang, Hui; Jing, Guoqing
Highlights: Quantified assessment of individual ballast degradation based on 3D particle images. Illustration of ballast breakage type and quantified using surface area change. Improvements in ballast surface texture quantification with 3D particle images. Reuse of waste rubber in railway engineering (ballast layer). Abstract: Higher speed, more freight and frequent maintenance increase ballast degradation and reduce the ballast lifespan. To reduce ballast degradation, crumb rubber used as buffering aggregates in ballast bed is relatively unexplored and needs more studies, because using it has the advantage of reusing the waster rubber and absorbing the noises. The effects of crumb rubber (CR) size and percentage on ballast degradation reduction is studied in this paper, and the optimal CR size and percentage are proposed. Three CR size ranges are utilised, i.e., 3 ∼ 5 mm, 10 ∼ 15 mm and 20 ∼ 25 mm, and the percentages are 0, 10, 20 and 30% by weight. Three kinds of ballast material with two size ranges are utilised. The deteriorated ballast particles were generated using Los Angeles Abrasion (LAA) tests, and the ballast degradation was evaluated with the 3D image analysis. The results indicate that ballast abrasion can be alleviated by adding the CR, while the CR has few influences on the ballast breakage. When CR size is close to ballast particle size, the effects of degradation reduction are not obvious. The corner and edge loss are the main types of ballast abrasion, although different ballast materials significantly influence the abrasion type and degree. Most importantly, the image analysis method is proved to have the ability to present ballast degradation process and has great potential for further degradation-related studies.